Food prices, processing, and shocks: Evidence from rice and COVID‐19. (12th October 2021) - Goeb, Joseph; Zone, Phoo Pye; Kham Synt, Nang Lun; Zu, A. Myint; Tang, Yulu; Minten, Bart
Abstract: Rice is the staple food for about half of the world's population and mills are the essential processing link between farmers and consumers, making rice milling one of the most important agro‐processing sectors globally. This paper assesses changes in rice and paddy prices, and processing margins during the COVID‐19 pandemic shock through the lens of rice mills in Myanmar. Our data, collected through telephone surveys with a large number of medium‐ and large‐scale rice millers in September 2020, reveal significant disruptions from the COVID‐19 pandemic, including transportation restrictions, employee lay‐offs, and reduced operations relative to normal times. However, milling margins, and paddy and rice prices were mostly stable, showing only minor increases compared to 2019. Rice prices increased most for the varieties linked to export markets, though the gains were mostly passed through to farmers as higher paddy prices. Similarly, higher rice prices achieved by modern mills—due to extra processing—were mostly transmitted to producers. Our results also highlight the major importance of byproducts—broken rice and rice bran—sales to overall milling margins as byproduct sales allowed mill operators to sustain negative paddy‐to‐rice margins.